Whatever happened to the F word in higher education?. Issue 2 (3rd March 2016) - Wright, T.
Abstract : As a women's studies academic who has taught health and social care students for four years in the UK, it strikes me that much of what and how I teach is incompatible with my own pedagogic position. At a time of government cuts and economic austerity there are ever shrinking opportunities to work in women's studies environments within the higher education academy, and I often find there is a mismatch between what I am offering as an academic and what an employer is looking for. Occupying the most junior teaching post on a fixed-term contract, and coming from the discipline of women's studies – constructed often as irrelevant and/or too political and controversial, rather than a necessary philosophical foundation to critical thinking – I have diminutive curriculum influence and find myself, more often than not, delivering hegemonic groups of theories and practice. Drawing largely on level 5 health and social care interprofessional learning module course materials, this paper will analyse the discourses inscribed within them, and consequently expose the essence of the learning and teaching that takes place within the classroom. This paper will also act as a catalyst to explore whether it is possible to find, or construct, a feminist space in my learning and teaching practice.